Antiobesity Effects of an Edible Halophyte Nitraria retusa Forssk in 3T3-L1 Preadipocyte Differentiation and in C57B6J/L Mice Fed a High Fat Diet-Induced Obesity. (3rd December 2013) - Zar Kalai, Feten; Han, Junkyu; Ksouri, Riadh; El Omri, Abdelfatteh; Abdelly, Chedly; Isoda, Hiroko
Abstract : Nitraria retusa is an edible halophyte, used in Tunisia for several traditional medicine purposes. The present study investigated the antiobesity effects of Nitraria retusa ethanol extract (NRE) in 3T3-L1 cells using different doses and in high-fat diet-induced obesity in mice. Male C57B6J/L mice were separately fed a normal diet (ND) or a high-fat diet (HFD) and daily administrated with NRE (50, 100 mg/kg) or one for 2 days with Naringenin (10 mg/kg). NRE administration significantly decreased body weight gain, fat pad weight, serum glucose, and lipid levels in HFD-induced obese mice. To elucidate the mechanism of action of NRE, the expression of genes involved in lipid and carbohydrate metabolism were measured in liver. Results showed that mice treated with NRE demonstrated a significant decrease in cumulative body weight and fat pad weight, a significant lowering in glucose and triglycerides serum levels, and an increase in the HDL-cholesterol serum level. Moreover mRNA expression results showed an enhancement of the expression of genes related to liver metabolism. Our findings suggest that NRE treatment had a protective or controlling effect against a high fat diet-induced obesity in C57B6J/L mice through the regulation of expression of genes involved in lipolysis and lipogenesis and thus the enhancement of the lipid metabolism in liver.